Plant soil seed bank analysis in wildfire former area of Mount Talang, West Sumatra, Indonesia - Indra Dwipa; CHIKA SUMBARI; ASWALDI ANWAR (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Dwipa I, Sumbari C, Anwar A. 2020. Plant soil seed bank analysis in wildfire former area of Mount Talang, West Sumatra, Indonesia. Biodiversitas 21: 155-160. Forest wildfire affects the ecosystems that live in it. One of them is plant ecosystem. One of forest wildfire occurred in Mount Talang, West Sumatra, Indonesia on February 1, 2018. This research aimed to study the soil seed bank that grew after wildfire in mount Talang. The sampling collection was done from former forest fire and natural forest. Germination of soil seed bank was conducted in the Laboratory of Seed Technology, Faculty of Agriculture and identification was conducted in Herbarium of Department of Biology, Faculty of Mathematics and Natural Science, Andalas University, Padang, Indonesia. Nested sampling was used in this study. Two natural forest and 2 former forest wildfire sites were used as sampling locations. Observation plot for sampling collection sized as 2 m x 2 m for sowing, 5 m x 5 m for stake, 10 m x 10 m for pole and 20 m x 20 m for tree. In plot, soil seed bank sampling was taken in 0-5 cm, 5-10 cm, 10-15 cm and 15-20 cm in depth. The result showed that 1 family and 14 plant-soil seed bank species were found in natural forest and 8 plant-soil seed bank was found in forest wildfire former area.